We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
262
2
avatar+874 

If \(f(x)=\dfrac{a}{x+2}\), solve for the value of a so that \(f(0)=f^{-1}(3a)\).

 Dec 9, 2018
 #1
avatar+103947 
+1

Let's find the inverse of f(x)

 

y =   a / ( x + 2)

 

y (x + 2) = a

 

yx + 2y = a

 

yx = a - 2y      divide both sides by y

 

x =  [ a - 2y] / y    "swap" x and y

 

y = [ a - 2x] / x      and this is the inverse = f-1(x)

 

Note that f(0) =  a /2

 

And f-1 (3a) =   [ a - 2(3a) ] 3a  =  -5a / 3a =   -5/3

 

 

So   we want to solve this

 

a/2  = -5/3

 

a =  -10/3

 

 

cool cool cool

 Dec 9, 2018
 #2
avatar+23140 
+10

If

\(\large{f(x)=\dfrac{a}{x+2}}\),

solve for the value of a so that

\(\large{f(0)=f^{-1}(3a)}\).

 

\(\begin{array}{|rcll|} \hline f\left(~ f^{-1}(x) ~\right) &=& x \quad & | \quad x = 3a \\ f\left(~ f^{-1}(3a) ~\right) &=& 3a \quad & | \quad f^{-1}(3a) = f(0) \\ f\left(~ f(0) ~\right) &=& 3a \quad & | \quad f(0) = \dfrac{a}{0+2}=\dfrac{a}{2} \\ f\left(~ \dfrac{a}{2} ~\right) &=& 3a \quad & | \quad f\left(\dfrac{a}{2} \right) = \dfrac{a}{\dfrac{a}{2}+2}=\dfrac{2a}{a+4} \\ \dfrac{2a}{a+4} &=& 3a \\ \dfrac{2 }{a+4} &=& 3 \\ 2 &=& 3 (a+4) \\ 2 &=& 3a+12 \\ 3a &=& -10 \\ \mathbf{a} &\mathbf{=}& \mathbf{-\dfrac{10}{3}} \\ \hline \end{array}\)

 

laugh

 Dec 10, 2018

31 Online Users

avatar
avatar
avatar
avatar
avatar